ANALISIS FAKTOR YANG MEMPENGARUHI KUALITAS HASIL AUDIT DI INSPEKTORAT JENDERAL KEMENTRIAN PERTANIAN - susanto, imam (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
The purpose of this study is to examine and analyze the extent to which the influence of Auditor Competence, Auditor Independence and Professional Ethics on the Quality of Audit Results. The research was done by quantitative approach. The population in this study is all auditors and prospective auditors at the Inspectorate General of the Ministry of Agriculture of the Republic of Indonesia amounted to 160 people. Sampling technique is done by simple random sampling with the number of samples of the study amounted to 115 respondents Data analysis techniques in this study using multiple linear regression analysis. The result of the research shows that there is no significant influence between the auditor's competence with the quality of the audit result and there is no significant influence between the auditor independence and the quality of the audit result. While professional ethics significantly influence the quality of audit results. Together the competence, independence and professional ethics affect the quality of audit results. For further research is expected to use a questionnaire with a wider coverage and expected to use more variables that affect the quality of audit results.